Transformation of the Single Tuition Fee (UKT) Policy : Effects of Campus Autonomy - Baharuddin Baharuddin; Lusiana Lusiana (International Journal of Educational Evaluation and Policy Analysis, 2025)
Campus autonomy in Indonesia provides good hope, but there are also many basic problems that disturb the hearts of the people, Especially those related to financial allocation. This study aims to examine the impact of campus autonomy on the implementation of the Single Tuition Fee (UKT) at the State Islamic University of Jakarta, community absorption of UKT, and its adaptation process. The research methodology will involve an in-depth analysis of campus autonomy policies and UKT implementation using naturalistic qualitative methods focused on a case study approach. Data was collected through in-depth interviews with key informants, namely university leaders, lecturers, students, and related stakeholders (n = 19). The data obtained are analyzed thematically. The results of the study are expected to provide a deeper understanding of the relationship between campus autonomy and UKT policies, community absorption, and its adaptation process to higher education accessibility and student experience. Data analysis will include stakeholder perceptions, changes in administrative policies and practices, and the social and economic impacts of UKT implementation. This study will summarize the main findings and their implications for the implementation of higher education management at UIN Jakarta. This research explains important implications for improving the effectiveness of campus autonomy implementation and UKT policies and provides guidance for decision-making at the institutional and government levels.